Karakteristik Anak Penderita PJB dengan Pirau Kiri ke Kanan Disertai Pembesaran Ventrikel Kiri di RSPAL dr.Ramelan - Fitria Maharani Subroto, Inggrid; Rokhmadoni Pikir, Rizqi; Risma; Diarsvitri, Wienta (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Congenital Heart Disease (CHD) is one of the most common congenital disabilities, with an incidence of 8-10 per 1000 live births in full-term infants and ten times higher in preterm infants. In Indonesia, the incidence of CHD is estimated at around 8 per 1000 live births. Understanding the anatomy and pathophysiology of the defect that occurs contributes to the accuracy of management planning. Purpose: This study aims to identify the characteristics of pediatric patients with CHD featuring left-to-right shunt accompanied by left ventricular enlargement at RSPAL dr. Ramelan Surabaya from 2020 to 2023. Methods: The descriptive study uses secondary data (medical records) of pediatric CHD patients with left-to-right shunt and left ventricular enlargement, specifically focusing on ventricular septal defect (VSD) and patent ductus arteriosus (PDA) at the pediatric clinic of RSPAL dr. Ramelan. Results: Based on medical records from 45 samples, the majority of CHD patients were aged 1-12 months (23 children). CHD with VSD was more common in males (18 children), while PDA was more common in females (11 children). Most CHD patients showed no initial complaints (39 children) and did not have other types of congenital heart diseases, with 23 children having VSD and 10 having PDA. Additionally, most patients did not have comorbidities (39 children). Echocardiographic results indicated that most patients had an ejection fraction (EF) greater than 75% (27 children) and a fractional shortening (FS) greater than 45% (23 children). The main management involved echocardiographic evaluation and medication. Conclusion: The predominant age group for CHD cases at the pediatric clinic of RSPAL dr. Ramelan was 1-12 months, with echocardiographic results showing normal left ventricular function, with EF >75% and FS >45%.